INTEGRATING ARTIFICIAL INTELLIGENCE INTO ENGLISH LANGUAGE TEACHING: A METHODOLOGICAL APPROACH TO DEVELOPING STUDENTS’ WRITING AND SPEAKING COMPETENCIES - Jabborberganova Hurriyat. (TADQIQOTLAR, 2026)
Abstract: This work presents a comprehensive methodological approach to the integration of artificial intelligence (AI) into English language teaching (ELT), with a focus on enhancing students’ writing and speaking competencies. The discussion unpacks the evolving role of AI-driven tools, their pedagogical implications, benefits, challenges, and critical considerations for sustainable implementation in various educational contexts. Special attention is paid to the effectiveness of AI in personalized instruction, feedback mechanisms, collaborative and communicative competence development, and student motivation. The work draws on recent academic research, practical case studies, and theoretical frameworks to propose a holistic, ethical, and inclusive strategy for integrating AI into ELT. The conclusion highlights future prospects and challenges, and the reference section offers recent studies to guide further exploration.